PENGARUH CAPITAL INTENSITY DAN SALES GROWTH TERHADAP TAX AVOIDANCE DIMODERASI OLEH PROFITABILITAS PADA SEKTOR CONSUMER CYCLICALS DI BEI TAHUN 2020-2022 - Anugrah, Yonathan Tri; Siagian, Valentine (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2023)
The test conducted in this study aims to determine whether there is an effect of capital intensity and sales growth on tax avoidance moderated by profitablity with quantitative methods. The data source used in this study uses secondary data sources, namely financial reports from companies with the consumer cyclical sector on the Indonesia Stock Exchange in 2020-2022, the observation sample in this study was drawn using a purposive sampling method totaling 130 observation samples. The results of testing companies in the consumer cyclicals sector in 2020-2022 found that capital intensity has no effect on tax avoidance with a result of 0.201, sales growth also has no effect on tax avoidance where the result is 0.130, while profitability affects tax avoidance with a result of 0.000, profitability as a moderator is unable to strengthen the effect of capital intensity on tax avoidance with a result of 0.649 and profitability as a moderator is not able to also strengthen the effect of sales growth on tax avoidance where the test result is 0.450.